Prolonged infection with hepatitis B virus and association between low blood cholesterol concentration and liver cancer. - Chen, Z; Keech, A; Collins, R; Slavin, B; Chen, J; Campbell, T; Peto, R (1993)
OBJECTIVE: To determine whether prolonged infection with hepatitis B virus is associated with a lower blood cholesterol concentration. DESIGN: Cross sectional study. SETTING: 81 villages in rural China with a high prevalence of chronic infection with hepatitis B virus. SUBJECTS: 1556 apparently healthy men aged 35-64 years, randomly selected. MAIN OUTCOME MEASURES: Hepatitis B virus carrier state; plasma concentrations of cholesterol, apolipoprotein B, and apolipoprotein A I. RESULTS: 238 (15%) of the men were positive for hepatitis B surface antigen, indicating that they were chronic carriers. Plasma concentration of cholesterol was 4.2% (0.11 mmol/l) lower among carriers (that is, positive for hepatitis B surface antigen) than among non-carriers (95% confidence interval 0.6% to 8.0% (0.01 to 0.21 mmol/l), p < 0.05), and apolipoprotein B concentration was 7.0% (0.036 g/l) lower (2.8% to 11.2% (0.014 to 0.058 g/l), p < 0.001). In contrast, no association was observed between plasma concentrations of cholesterol or apolipoprotein and hepatitis B that had been eradicated (that is, patient positive for hepatitis B core antibody but negative for hepatitis B surface antigen). CONCLUSIONS: Chronic hepatitis B virus infection, which usually starts in early childhood in China, seems to lead not only to a greatly increased risk of death from liver disease but also to a somewhat lower cholesterol concentration in adulthood. This common cause produces an inverse association between cholesterol concentration and risk of death from liver cancer or from other chronic liver diseases.